The students' difficulties in understanding the authentic news items materials in the listening class - Allvian I. F. Susanto (English Language and Education Spectrum, 2021)
This objective of the research is to identify the difficulties faced by the students in understanding the authentic listening materials of the news item. The participants of the research are the second-semester undergraduate Students of the English Education Department (EED) in Universitas Nasional Karangturi Semarang 2020/2021. The research method applied in this research setting is the descriptive method. Six students are participating in this research. To collect the data of the research, a questionnaire was used. The data collected was analyzed descriptively by identifying the responses of the questionnaire to identify further the difficulties faced by the research participants. The result of the research shows that the participants, majorly, face difficulties in understanding each part of the authentic news item materials. The difficulties faced by participants are caused by the rate or speed of the native speakers’ talk, the participants’ vocabulary unfamiliarity, lack of vocabulary mastery, and listening strategy.